Effect of Mineral Mixture Supplementation on Productive and Reproductive Performance of Buffaloes under Farmer FIRST Project - Y. S. Jadoun; Jaswinder Singh; J.S. Hundal; R. Kasrija; S.K. Kansal; R. K. Sharma; Navkiran Kaur (Indian Journal of Animal Nutrition, 2024)
Providing adequate nutrition is one of the crucial factor in maintaining proper biological, immunological, productive and reproductive traits of milch animals so, the current study was carried out in 2022 to find out the effect of mineral mixture supplementation on productive and reproductive performance of  buffaloes under Farmer FIRST Project : Integrated Approaches for Livestock Development : Farmers Context, implemented by ICAR. Under this project five villages namely Mehal Kalan, Moom, Channanwal, Dhaner and Kalala of Mehal Kalan block of Barnala district of Punjab are adopted. A total of 100 beneficiary farmers from these five villages were selected and mineral mixture was given free of cost under the project, then data on the effect of mineral mixture supplementation on productive and reproductive performance of buffaloes were collected and analyzed with the help of relevant statistical tools. Results revealed that average daily milk yield, peak milk yield and lactation yield increased significantly (P